Pengaruh Motivasi Terhadap Produktivitas Ormas Aisyiyah Muhammadiyah Surabaya - Yadila Fany Asrofi; Aulia Dila Agustina; Sentot Imam Wahjono (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the extent of the influence of motivation on the productivity of cadres and members of Aisyiyah Muhammadiyah Community Organization in Surabaya. Through a descriptive qualitative approach and literature study, it was found that intrinsic and extrinsic motivation are the main factors in increasing active participation and effectiveness of organizational work programs. Motivational aspects such as religious values, social encouragement, non-material incentives, and recognition of contributions are proven to influence members' activeness in carrying out da'wah, social, educational, and health programs. These findings confirm the importance of motivation-based empowerment strategies to increase the productivity of religious community-based organizations.